PENGARUH PERAN WALI KELAS (SEBAGAI PENGGANTI GURU BIMBINGAN KONSELING) TERHADAP DISIPLIN BELAJAR SISWA - Putri Anjani; Rasmitadila; Novi Maryani; Muhammad Rendi Ramdhani (Fakultas Agama Islam dan Pendidikan Guru, 2022)
This research aims to know Impact between the role of homeroom teacher as substitute Counseling teacher to student learning discipline of grade 5 in Elementary School at Depok City. This researches is a type of quantitative researches with functional correlation and simple regression analysis. population in school research in Depok city consists of homeroom teacher in SDN Sukamaju Baru 1, SDN Sukamaju Baru 5, SDN Cilangkap 4,and SDN Sukamaju 10 and also students of grade 5 in SDN Sukamaju Baru 1. Sampling technique used Probability Sampling with random sampling. As many samples are used 7 the homeroom teacher and 70 students. Test hypotheses using correlation tests of Product moment from Pearson with the help of calculations using the program SPSS version 16.0, with the conclusion that there is no influence of the role of homeroom teacher as a substitute for teacher counseling guidance on learning discipline.